A Comparison of Monolingual and Sequential Bilingual Tertiary Level Students on the Relationship Between Analytic Language Knowledge and Metalinguistic Awareness - Baytar, Birtan; Çakır, İsmail (University of Ljubljana, 2022)
Analytic language knowledge has often been highlighted among experts in the field, and its potential effects on metalinguistic awareness have been of great interest to researchers. This study aims to find the relationship between analytic language knowledge and its potential effect on metalinguistic awareness. A total of 210 tertiary level students from three different public universities in Turkey participated the study. The subjects were studying in three different departments: History and Philosophy (i.e., with no analytic language abilities and monolinguals), Turkish Language and Literature (i.e., studying Turkish, their mother tongue, analytically and monolinguals), and English Language Teaching and English Language and Literature (i.e., studying English, their second language, analytically and sequential bilinguals). The participants were asked to complete a demographic questionnaire and a test (adapted from Ter Kuile et al., 2011) written in Indonesian in order to evaluate their metalinguistic awareness, and the results were compared among the departments. The data gathered through the questionnaires were analysed using IBM SPSS 22. The results show that the participants from English Language Teaching and English Language and Literature performed significantly better than the other two groups. No significant difference was found between the History, Philosophy and Turkish Language and Literature departments. The present findings empirically revealed that sequential bilinguals have a greater degree of metalinguistic awareness, and thus alternative curricula for different departments may be adopted in terms of supplementary language courses, and this is one of the implications of this study for future research. Students who have a background in multiple languages, for instance, may be able to enrol in additional language lessons under a plan that is developed by taking metalinguistic abilities into account.
Keywords: sequential bilinguals; P1-1091; analytic language knowledge; metalinguistic awareness; Philology. Linguistics; 4. Education; 16. Peace & justice